2016
DOI: 10.1167/iovs.15-18618
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pattern of Macular Ganglion Cell-Inner Plexiform Layer Defect Between Ischemic Optic Neuropathy and Open–Angle Glaucoma

Abstract: Patients with NAION show differences in the tissue damage with greater loss of parafoveal GCIPL tissue thickness compared to patients with POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…In this cross-sectional study using spectral-domain OCT (Cirrus; Carl Zeiss Meditec, Dublin, CA, USA), we analysed both sectoral RNFL and sectoral GCIPL in primary open-angle glaucoma (POAG) patients and stabilised, unilateral NAION patients. Similar to our study, Fard et al [ 13 ] compared patterns of GCIPL defects between POAG and NAION using another spectral-domain OCT device (Spectralis; Heidelberg, Jena, Germany). In their study, to match the severity of optic disc damage in NAION, moderate-to-severe POAG cases (mean deviation [MD] on visual field examination < -6.0 dB) were selectively enrolled.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In this cross-sectional study using spectral-domain OCT (Cirrus; Carl Zeiss Meditec, Dublin, CA, USA), we analysed both sectoral RNFL and sectoral GCIPL in primary open-angle glaucoma (POAG) patients and stabilised, unilateral NAION patients. Similar to our study, Fard et al [ 13 ] compared patterns of GCIPL defects between POAG and NAION using another spectral-domain OCT device (Spectralis; Heidelberg, Jena, Germany). In their study, to match the severity of optic disc damage in NAION, moderate-to-severe POAG cases (mean deviation [MD] on visual field examination < -6.0 dB) were selectively enrolled.…”
Section: Introductionsupporting
confidence: 75%
“…[ 42 ] While papillomacular nerve fibre bundles are spared in this region until a late stage in POAG, they are generally damaged in NAION. [ 13 , 42 , 43 ] The higher incidence of ischaemic events in the superior region in NAION, and less profound damage in the superior region in POAG, may also support this. [ 29 , 34 37 , 39 , 40 ] However, in our study, there was no difference in the inferior or inferotemporal GCIPL sectors between NAION and POAG.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…14,15 Moderate and severe POAG eyes with Humphrey 24-2 mean deviation of less than -6 dB were recruited, so that the glaucoma and NAION groups would be similar in terms of severity. 1,14,15 Presence or absence of peripapillary atrophy was not an inclusion or exclusion criterion.…”
Section: Methodsmentioning
confidence: 99%
“…The thickening of Gc-IPL in the central 1 mm may be due to intracellular edema due to greater ischemic stress on central fovea in the early phase of NAION and contributes to vision deterioration. Fard et al [27] reported that parafoveal Gc-IPL thinning present in chronic NAION eyes was associated with worse vision compared to glaucoma patients in which central vision is preserved and has no Gc-IPL thinning in this area. Parks et al reported the initial thinning of Gc-IP layer in the macula occurring 46.1 ± 23.2 days after the onset of NAION symptoms.…”
Section: Discussionmentioning
confidence: 99%